Evidence Supporting Open-Loop Control During Early Vergence - John Semmlow; Tara Alvarez; Bérangère Granger-Donetti (Bern Open Publishing, 2013)
Disparity vergence eye movements were analyzed to determine if the early component of this response operates under open-loop, or preprogrammed, control. The analysis compares ratios of peak velocity to response amplitude (i.e., main sequence ratios) for the isolated early component and for the entire disparity vergence response. The stimuli were limited a 4 deg step changes in vergence so that any differences in movement dynamics (i.e., peak velocities) were due only to internal noise. Nine binocularly normal subjects were studied. A significant correlation between peak velocity and amplitude was observed during the early portion of the movement (p < 0.002), but not for the overall vergence response. Results support the widely held, but unproven assumption that the early component of symmetrical vergence is guided by open-loop, or preprogrammed, control processes while the overall response is influenced by internal and/or external feedback.